Broken Home - SULISTIYANTO, Ari (FSR ISI Yogyakarta, 2017)
Every child has the right to grow and to develope their potentials. Their parents have the responsibility for that matter. Parents are the fundamental aspect in a family. Building a family is also based on each family member’s needs. A family is a uit system formed from three primary structure, a father/husband, a mother/wife, and children. Family is the first place where a child gets experiences to live their own life. So please dont broke our family down. For all broken home child, keep moving on your life and keep working on whatever you want to do.Kata kunci: broken home, keluarga, perceraian, seni grafis